Eseistyczna chopinologia Piotra Wierzbickiego - Lisak-Gębala, Dobrawa (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
Piotr Wierzbicki’s deep interest in Chopin’s music has been revealed in his volumes of essays published since 1993. What appears to make his music writings exceptional in comparison with other Polish essays dealing with Chopin’s life and work is the prevailing concentration on particular pieces or even single performances chosen by famous pianists. Wierzbicki develops his project of extradisciplinary essayistic Chopinology that blends together the musicological knowledge, critical involvement, philosophical reflection and highly individual psychosomatic experience. Having stated a fundamental difficulty of ‘translating’ sounds into words, he tries to elaborate a ‘musical’ style and form for his writing, e.g. he includes ekphrases full of metaphors and synesthetic figures. This wide array of music-centred properties encourages readers to treat these essays as a starting point for coming up with the question of whether it is possible to differentiate a type of ‘musical’ essay.